EVALUATION OF ASSOCIATION BETWEEN OXIDATIVE STRESS PARAMETERS AND PESTICIDE EXPOSURE IN CASE OF RECURRENT PREGNANCY LOSS AMONG - AKANCHA PANDEY; S.P.JAISWAR; MOHD. KALEEM AHMAD; MOHD. WASEEM (International Journal of Pharma and Bio Sciences, 2016)
Recurrent pregnancy loss (RPL) is defined as 3 or more consecutive pregnancy losses prior to 20th week of gestation.The prevalence of recurrent pregnancy loss is 1% to 3% of pregnancies. RPL is a challenging medical problem because of its unknown pathogenesis and etiology in most of the cases .Environmental contaminant may adversely affect the human reproductive health includes heavy metals, pesticides and other agents.The present study was conducted to investigate possible associations of pesticide exposed oxidative stress in the pathogenesis of RPL. Seventy women with two or more consecutive pregnancy losses were enrolled along with healthy women having one or more healthy and live issue as controls (70). The complete plasma lipid peroxidation products, enzymatic and non-enzymatic antioxidants were measured according to respective protocols. The levels of antioxidant enzymes namely catalase, superoxide dismutase, glutathione peroxidase, glutathione reductase were significantly reduced in cases. However, the level of lipid peroxides, protein carbonyls and conjugated dienes were found significantly increased in all patients who experienced recurrent pregnancy loss. On the basis of our results, it may be concluded that pesticide exposure tends to increase oxidative stress with the increase of pro-oxidant components, which may result in various complications including peroxidation of vital body molecules resulting in increased risk for recurrent pregnancy loss.